Screening and diagnosis of gestational diabetes mellitus by IADPSG criteria - Chaudhary, Gunjan; Raghunandan, Chita; Chopra, Kanika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: GDM is a complex clinical entity and its screening, diagnosis, and management warrants attention. With this issue in mind, we aimed to study the prevalence of gestational diabetes mellitus in the antenatal group of patients attending tertiary hospital in New Delhi and its association with maternal outcome. Methods: 300 pregnant patients were enrolled in the first trimester and RBS (random blood sugar) was done. Those who had RBS >200mg/dl were labelled as overt diabetes and excluded from the study. The patients who were screened negative in phase 1 of screening were subjected to the next phase of screening at 24-28 weeks of gestation with 2-hour 75g OGTT using IADPSG criteria. Those who were diagnosed as GDM were followed in the antepartum, intrapartum and postpartum period. Results: The prevalence of overt diabetes and GDM in the study population is 1.33% and 13.33%. The prevalence of gestational hypertension, pre-eclampsia, chronic hypertension, polyhydramnios was 15%, 5%, 5%, 7.5% respectively. Normal and instrumental vaginal delivery was in 50 %, 5% patients respectively and 45 % had the caesarean section. Conclusions: The single step OGTT with lower threshold value cut-offs and single abnormal value for the diagnosis of GDM as advocated by IADPSG seem to be effective as it helps to screen and diagnose GDM at the same time as a single step procedure and thus more cost-effective.